A Study on Commuting Therapy, Designing a Human-Vehicle Interaction System to Enhance the Commuting Experience with Emotion-Based Multisensory Strategies - Lu, Xiaonan (My University, 2024)
Commuting is often perceived as mundane and time-consuming. However, commute also offers an opportune space and time for design interventions that can enhance well-being during the daily commute. This thesis project explores the design opportunities to enhance the leisure experience during commuting, with a focus on Jordan’s Four Product Pleasures. This project reimagines commute as a transition period aimed at improving human well-being, transforming it into a more pleasurable experience. As a result, this project introduces an affective human-vehicle interaction system within the smart cabin, employing multisensory emotion regulation strategies, including vision, aroma, music, and haptics. Specifically, this project details the design of a multisensory experience tailored to driver emotional states during commutes. The proposed design was evaluated through a VR car simulator in a qualitative user study, which revealed user preferences for multisensory experiences.
Keywords: Commute; Driver’s Emotional States; Emotion regulation; Multisensory Experience; Well-being